Facile Fabrication and Properties of Super-hydrophobic MgAl-LDH Films With Excellent Corrosion Resistance on AZ31 Magnesium Alloy - Han, Xing; Hu, Jia; Wang, Yong-Qin; Xiao, Tian-Bing; Xia, Wei; Chen, Yan-Ning; Wu, Liang (Frontiers in Materials, 2021)
A super-hydrophobic anti-corrosion film was facilely prepared via in-situ growth of layered double hydroxides (LDHs) on the etched AZ31 magnesium alloy and then modification by 1H, 1H, 2H, 2H-perfluorooctyltrimethoxysilane (PFOTMS) in this work. The morphology, structure, composition, surface roughness and water contact angles (WCA), and the anti-corrosion performance of the samples were investigated. The results revealed that the micro/nano hierarchical surface morphology of the films was composed of island structures obtained after chemical etching and MgAl-LDH nanowalls grown in situ. The best hydrophobicity (CA=163°) was obtained on the MgAl-LDHs with the maximum surface roughness. Additionally, the potentiodynamic polarization, electrochemical impedance spectroscopy and immersion test indicated that the super-hydrophobic LDH films provided better corrosion resistance to AZ31 Magnesium alloy due to the double-protection derived from the LDHs and super-hydrophobic properties. Furthermore, the contact angle could be kept at above 140° after dipped in 3.5 wt % NaCl solution for 6 days.